2008
DOI: 10.1371/journal.pcbi.1000184
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Bistability Generates hunchback Expression Sharpness in the Drosophila Embryo

Abstract: During embryonic development, the positional information provided by concentration gradients of maternal factors directs pattern formation by providing spatially dependent cues for gene expression. In the fruit fly, Drosophila melanogaster, a classic example of this is the sharp on–off activation of the hunchback (hb) gene at midembryo, in response to local concentrations of the smooth anterior–posterior Bicoid (Bcd) gradient. The regulatory region for hb contains multiple binding sites for the Bcd protein as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 79 publications
(145 reference statements)
8
108
0
6
Order By: Relevance
“…In addition, ultrasensitivity can increase the robustness of bistable responses141516 and can stabilise biological oscillations17181920212223242526. Finally, ultrasensitivity has been shown to play a major role in converting spatial gradients into sharp boundaries in morphogenesis and developmental patterning27282930313233. In the latter context, our previous work showed that steeper dose-response functions better supported Turing pattern formation in a theoretical developmental model28.…”
mentioning
confidence: 98%
“…In addition, ultrasensitivity can increase the robustness of bistable responses141516 and can stabilise biological oscillations17181920212223242526. Finally, ultrasensitivity has been shown to play a major role in converting spatial gradients into sharp boundaries in morphogenesis and developmental patterning27282930313233. In the latter context, our previous work showed that steeper dose-response functions better supported Turing pattern formation in a theoretical developmental model28.…”
mentioning
confidence: 98%
“…52,67 This makes modeling of P1 and P2 output somewhat conjectural (though the technology is available to distinguish the transcripts 16 ). Given this, however, our approach o®ers a means whereby the knowledge we have of the hb cis-architecture (CRMs, transcription start sites) can be turned into a dynamic model for expression patterning.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a stochastic model of Bcd and Hb (self) activation of the anterior hb expression domain [43], developed from an earlier deterministic version [44], predicted that reporter constructs with less than wild-type numbers of Bcd BSs should show increased variability of the mid-embryo boundary, and that loss of hb autoregulation should decrease correlation of the FISH signal between the two hb gene copies (dots). See also Sanchez et al and Monteoliva et al [40,45] on the effect of the number of BSs on transcriptional noise.…”
Section: Modelingmentioning
confidence: 99%